Application of Search Model to Detect Urhobo Names in Niger Delta Region of Nigeria: A Preliminary Study - OKWONU, FRIDAY ZINZENDOFF (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
This paper is designed to determine the accuracy of search words or names from a database using search vector. Generally, database consists of large collection of information. By specifying the search words or names this model is able to retrieve the required information from the database relying strictly on the search vector. In this regards, the target names are assigned one if the names corresponds to the search vector and zero otherwise. This information is applied to develop the target matrix. Based on the target matrix, we can determine precisely the number of names that corresponds to the different name books. To further analyze the performance of this technique, the model is validated by post multiplying the variance by the target mean. The result revealed that the search model was able to detect accurately the required names.